Higher Levels of Postoperative Mobility and Activity as Measured by the AM-PAC 6 Clicks Instrument Are Associated with Improved Outcomes after Lumbar Fusion - Parimal Rana; Jane C. Brennan; Andrea H. Johnson; Justin J. Turcotte; Chad M. Patton (Spine Surgery and Related Research)
Introduction: Previous studies have shown that early patient mobility and activity can improve patient outcomes after lumbar fusion procedures. This study aimed to explore the relationship between patient mobility and activity, measured by the Activity Measure for Post-acute Care (AM-PAC) “6-Clicks” assessment and postoperative outcomes in lumbar fusion patients. Methods: A retrospective review of 306 lumbar fusions (105 with 6-Clicks mobility and 289 with 6-Clicks activity scores) was conducted. Statistical analyses were performed to evaluate the relationship between 6-Clicks scores and postoperative outcomes, such as prolonged length of stay (LOS), nonhome discharge, 30-day emergency department (ED) returns and readmissions, and minimal clinically important difference (MCID) achievement on the PROMIS-PF instrument at 3-12 months postoperatively. Results: After controlling for age, body mass index, sex, race, number of levels, and preoperative PROMIS-PF, higher 6-Clicks mobility scores decreased the likelihood of 3+ day LOS (OR: 0.72; p=0.010), non-home discharge (OR: 0.68; p<0.001), and 30-day ED return (OR: 0.78; p=0.022) and increased the likelihood of PROMIS MCID achievement (OR: 1.28; p=0.004). The odds of LOS 3+ days, non-home discharge, and ED return for each one-point increase in mobility scores all decreased by 28%, 32%, and 22%, respectively, while the odds of achieving PROMIS MCID for every one-point increase in mobility increased by 28%. After risk adjustment, higher 6-Clicks activity scores were protective against 3+ day LOS (OR: 0.78; p<0.001) and non-home discharge (OR: 0.69; p<0.001). Conclusions: The AM-PAC 6-Clicks mobility and activity scores hold value as early indicators of prolonged LOS and nonhome discharge, while mobility scores may help identify patients who are at risk for ED returns and who fail to experience clinically significant improvement in physical function. These tools may be used to identify patients requiring additional resources and can inform discussions surrounding patient expectations.